SOCIOLINGUISTIC PERSPECTIVE OF GENDER PATTERNS ON FACEBOOK - Marissa Swanda Tupamahu (JURNAL TAHURI, 2018)
The purpose of this research is to look for the differences and similarities among the way sexes use internet particularly social networking site, Facebook. The differences exist on multiple levels and all these have been exhibited through language and the choices they make. The findings show that women mostly write about themselves, about their own emotions, andthe way a female leaves all information blank and a male give all for public display certainly speaks volumes about their privacy concerns.